A Sociological Analysis of Tourism Research in Pokhara, Nepal: Perspectives and Key Findings - Paudel, Mohan Kumar; Khatri, Shanta Kumari (The Himalayan Geographers, 2024)
This study explores the socio-cultural, economic, and environmental impacts of tourism in Pokhara, Nepal, and examines how sustainable tourism practices can be integrated into the region's development for long-term benefits. Tourism in Nepal, particularly in Pokhara, significantly contributes to the national economy by generating employment, stimulating local businesses, and promoting rural development. However, it also brings challenges such as cultural erosion, social inequalities, and environmental degradation. Despite the growing interest in sustainable tourism, there remain research gaps regarding the impacts on lesser-known areas, small and medium-sized enterprises (SMEs), and community-based tourism (CBRT). This research employs a systematic literature review and content analysis to address these gaps and provide insights into balancing tourism growth with sustainability. Key themes explored include the role of tourism in community participation, the economic benefits and challenges faced by marginalized groups, and the integration of sustainable practices. Findings indicate that while tourism in Pokhara has led to economic growth, it has also caused displacement of traditional livelihoods and widened socio-economic disparities. The study emphasizes the need for inclusive governance, participatory decision-making, and the implementation of sustainable tourism practices to mitigate these negative impacts. The research aims to offer recommendations for policymakers and tourism professionals to develop more sustainable, inclusive, and culturally sensitive tourism strategies, ensuring lasting benefits for both the community and the environment.